Students’ Difficulties, Perceptions, Feelings, and Types of Technology Used in Learning English - Amanda Pradhani Yanwar; Jirarat Sitthiworachart; Mike Joy (Journal of Higher Education Theory and Practice, 2025)
This study aimed to investigate students’ experiences in learning English. The secondary aim was to find out the types of technology students use when learning English. The data were collected by interviewing 15 undergraduate students enrolled on a Social and Political Science program. The interviews were audio-recorded, transcribed in Indonesian, translated into English, and analyzed to identify categories of the students’ difficulties, perceptions, feelings, and types of technology used when learning English. The study's results show the effectiveness of using a phenomenographic analysis, which may be used to create more interesting and meaningful English teaching and learning activities in second language environments. These could also be used by teachers to help them build the best possible curriculum for teaching second language students.
Keywords: EFL/ESL Teaching and Learning